School Heads' Leadership Practices and Administrative Psychological Attributes an the Post-Pandemic Readiness of San Pablo City Public Elementary Schools - Ofrin, Darius D. (Future Science / FSH-PH Publications, 2024)
School Leaders in the Philippines are confronted with unexpectedly high levels of hardship. The school leaders function is expansive in scope, extremely demanding, and time-sensitive (Riley 2015). Individual psychological traits are distinct aspects of a person that shape their actions and mindset. These traits encompass one's personality, temperament, cognitive abilities, and emotional conditions. Being prepared for school is crucial as it enables teachers to enhance and build upon a child’s abilities, particularly in social interactions. However, today's challenge to achieving school readiness stems from the disruptions caused by the pandemic. This research aims to determine whether public schools in San Pablo City are equipped to handle post-pandemic classes, focusing on factors such as the adequacy of instructional materials, quality of governance and leadership, efficiency of school operations, effectiveness of teacher performance, student engagement, and the level of parental involvement. vii This study is anchored on Distributed leadership by Edwin Hutchins, Hutchins’ theory, a conceptual and analytical approach how the work of leadership takes place distributed leadership is basically shared management and Goal setting theory for Leadership practices which state that for goals to be motivational, they have to be specific and challenging but yet attainable (Locke and Latham, 1990, 2002). The research revealed a strong connection between the leadership practices of school administrators and the school’s preparedness in various areas. These areas include establishing clear goals and expectations, allocating resources to meet these objectives, fostering high-quality teaching, promoting professional development for teachers, and maintaining a secure and organized learning environment. The study brought out that the public schools in San Pablo City elementary are prepared for the post pandemic classes in terms of instructional adequacy, leadership and governance , school operation, teacher performance, learners interest, and parental support. Ultimately, the study identified that the leadership practices and psychological administrative traits of school heads are key indicators of how prepared public schools in the San Pablo City Division are for the